Unveiling modernity in twentieth-century West African Islamic reforms - Kobo, Ousman Murzik. (Islam in Africa, 2012)
In this book Ousman Kobo analyzes the origins of Wahhabi-inclined reform movements in two West African countries. Commonly associated with recent Middle Eastern influences, reform movements in Ghana and Burkina Faso actually began during the twilight of European colonial rule in the 1950s and developed from local doctrinal contests over Islamic orthodoxy. These early movements in turn gradually evolved in ways sympathetic to Wahhabi ideas. Kobo also illustrates the modernism of this style of Islamic reform. The decisive factor for most of the movements was the alliance of secularly educated Muslim elites with Islamic scholars to promote a self-consciously modern religiosity rooted in the Prophet Muhammad's traditions. This book therefore provides a fresh understanding of the indigenous origins of "Wahhabism."